International cooperation group of emergency surgery during the COVID-19 pandemic - Yánez Benítez, Carlos (Eur J Trauma Emerg Surg, 2020)
PURPOSE: The COVID-19 pandemic has changed working conditions for emergency surgical teams around the world. International surgical societies have issued clinical recommendations to optimize surgical management. This international study aimed to assess the degree of emergency surgical teams’ adoption of recommendations during the pandemic. METHODS: Emergency surgical team members from over 30 countries were invited to answer an anonymous, prospective, online survey to assess team organization, PPE-related aspects, OR preparations, anesthesiologic considerations, and surgical management for emergency surgery during the pandemic. RESULTS: One-hundred-and-thirty-four questionnaires were returned (N = 134) from 26 countries, of which 88% were surgeons, 7% surgical trainees, 4% anesthetists. 81% of the respondents got involved with COVID-19 crisis management. Social media were used by 91% of the respondents to access the recommendations, and 66% used videoconference tools for team communication. 51% had not received PPE training before the pandemic, 73% reported equipment shortage, and 55% informed about re-use of N95/FPP2/3 respirators. Dedicated COVID operating areas were cited by 77% of the respondents, 44% had performed emergency surgical procedures on COVID-19 patients, and over half (52%), favored performing laparoscopic over open surgical procedures. CONCLUSION: Surgical team members have responded with leadership to the COVID-19 pandemic, with crisis management principles. Social media and videoconference have been used by the vast majority to access guidelines or to communicate during social distancing. The level of adoption of current recommendations is high for organizational aspects and surgical management, but not so for PPE training and availability, and anesthesiologic considerations.